A survey to investigate the heterogeneity of food date labelling and the consumer’s knowledge and practice on food date labelling in Bangi, Selangor, Malaysia - S.N., Mohd Fadzil; Nordin, Y.; Chang, W.S.; Loo, Y.Y.; Tan, C.W.; Kuan, C.H.; Ungku Zainal Abidin, U.F.; R., Son (Rynnye Lyan Resources, 2024)
There are different types of food date labelling for different groups of food. However, many food retailers did not follow the regulation and make consumer confuse. Besides, consumers are also not aware of the food date labelling. This study aimed to investigate the heterogeneity of food date labelling and storage instruction in the hypermarket and to investigate the consumers’ knowledge and practices on food date labelling. In this study, the usage of the expiry date of refrigerated food products which were pre-packed fruits and vegetables, cheese, milk, juices, cream, dessert, ice cream, yogurt, smoked beef, salami, roasted beef and meat, and chicken loaf and salad dressing were analyzed. The frequency of the shelf life label was enumerated. There were 44.3% of refrigerated food products using the ‘best before’ date while 23.9% used ‘use by’ date. Besides, there were 53.4% of the refrigerated food products with storage instructions while 14.9% of it did not have any storage instructions. Questionnaires were used to study the knowledge and practice of consumers towards food date labelling from 385 respondents in Hulu Langat, Selangor. Findings showed that 45.97% of the respondents were not aware about food date labelling but 47.01% of the consumer use shelf life label to judge the edibility of food products. There were 33.77% of the respondent who did not know the difference of food date labelling. Consumers should understand the difference of food date labelling to reduce the number of food waste and food borne disease. The number of consumers who are confused and not aware of food date labelling are worrying. It is recommended for the retailer to use the standardized label for food. © 2024 The Authors. Published by Rynnye Lyan Resources.